T1 Fluticasone propionate alters the resident airway microbiota and impairs anti-viral and anti-bacterial immune responses in the airways. (12th November 2015) - Singanayagam, A; Glanville, N; Pearson, R; James, P; Cuthbertson, L; Cox, M; Moffatt, M; Cookson, W; Bartlett, N; Johnston, S
Abstract : Background: Inhaled corticosteroids are the cornerstone of therapy in asthma and COPD but cause only modest reduction in exacerbations and are associated with increased pneumonia frequency. This has raised concern about potential detrimental effects on host-defence against respiratory pathogens. The aim of this study was to evaluate the effects of fluticasone propionate on airway anti-viral and anti-bacterial host-defence. Methods: C57BL/6 mice were intranasally treated with fluticasone propionate (1 mg/kg) or vehicle control. 16S Quantitative PCR was used to evaluate total bacterial loads and pyrosequencing was used to evaluate microbiota community composition in lung tissue. Using mouse models of infection with rhinovirus 1B and S. pneumoniae D39, effects of fluticasone administration on anti-viral and anti-bacterial immune responses, airway inflammation and pathogen control were evaluated. Results: Mice treated with fluticasone had increased lung bacterial loads compared to vehicle-treated controls at 8 h post administration (p < 0.05). Evaluation of community composition revealed that fluticasone treatment was associated with significant increases in Stenotrophomonas genera (p < 0.05). In a mouse model of S. pneumoniae infection, fluticasone administration suppressed anti-bacterial responses including expression of cytokines IL-6 and TNF-α (4 h post-infection; p < 0.001) and airway neutrophil recruitment (8 h post-infection; p < 0.001) and was also associated with increased lung bacterial loads measured by quantitative culture (8 h post-infection; p < 0.001). In a mouse model of rhinovirus infection, fluticasone suppressed innate anti-viral responses including BAL protein levels of interferon-β and -λ2/3 (day 1 post-infection; p < 0.001). Virus clearance was impaired by fluticasone with increased viral RNA copies observed in lung tissue (day 1&2 post-infection; p < 0.001). The late expression of rhinovirus-induced airway mucins MUC5AC and MUC5B BAL proteins was increased by fluticasone (p < 0.01 and p < 0.05 respectively at day 7). Administration of recombinant interferon-β in combination with fluticasone and rhinovirus led to upregulation of interferon-stimulated genes and improved virus clearance, thereby demonstrating that adverse effects of fluticasone on RV clearance are causally related to interferon suppression. Recombinant IFN-β did not alter the increased mucins observed with fluticasone treatment. Conclusion: Fluticasone alters the airway microbiota and impairs airway anti-viral and anti-bacterial host-defence in mice. Human studies are required to confirm the relevance of these effects in the context of inflammatory airway diseases.